Reliability and validity of Chinese version of a tool to assess the quality of life in idiopathic pulmonary fibrosis in patients with interstitial lung disease - Rui-Li Pan; Jeffrey J. Swigris; Yan-Wei Zhao; Ai-Min Guo; Qing Wu; Si-Jia Li (Elsevier, 2019)
Objective: This paper aims to determine the reliability and validity of the Chinese version of a tool that assesses the quality of life in idiopathic pulmonary fibrosis (cATAQ-IPF) in patients with interstitial lung disease (ILD). Methods: We used the process of scale introduction to establish cATAQ-IPF. The content validity of the scale was evaluated by six experts. A total of 92 patients with ILD completed the cATAQ-IPF, St. George's respiratory questionnaire (SGRQ), and The Medical Research Council dyspnoea scale at the baseline, and 15 patients completed cATAQ-IPF at the follow-up period 2 weeks later. Thus, yielding data were used to assess various psychometric properties of cATAQ-IPF. Intraclass correlation coefficient (ICC), Cronbach's α coefficient, content validity index (CVI), item-level CVI (I-CVI), Pearson's coefficients, criterion-relation validity, and known-group validity were used for data analysis. Results: The cATAQ-IPF showed excellent test-retest reliability (ICC = 0.95), except for the therapy domain (Cronbach's α = 0.60) and acceptable internal consistency (Cronbach's α = 0.96 for the total). The scale-level CVI was 0.80, and the I-CVI was in the range of 0.78-1.00. The total cATAQ-IPF score was strongly correlated with the SGRQ total score (r = 0.71, P < 0.01). The cATAQ-IPF score of patients with ILD was 250.74 ± 47.39, and that of patients with IPF was 287.90 ± 22.56. Patients with IPF possessed considerable impairments in health-related quality of life according to the cATAQ-IPF score (t = 4.94, P < 0.01). Conclusions: The cATAQ-IPF is a reliable and valid instrument for the evaluation of quality of life of Chinese patients with various forms of ILD. Keywords: Health related quality of life, Interstitial lung disease, ATAQ-IPF, Reliability, Validity